Mammary gland development and lactation in a juvenile female of cuvier’s beaked whale (Ziphius cavirostris) with an ovarian granulosa cell tumour - Espinosa De Los Monteros Y Zayas, Antonio; Herráez Thomas, Pedro Manuel; Alves Godinho, Ana; Jáber Mohamad, José Raduán; Arbelo Hernández, Manuel Antonio; Fernández Rodríguez, Antonio Jesús (2007)
Ovarian tumours are classified on the basis of the cell of origin as epithelial tumours, germ cell tumours and stromal tumours. In this latter group is included the granulosa cell tumour, the most common ovarian neoplasm in domestic animals. Granulosa cell tumours may secrete a variety of hormones, including progesterone, oestrogen, testosterone and inhibin. The production of hormones is frequently associated with abnormal behaviour and physiological events. In cetaceans, granulosa cell tumours have been described only in four species of cetaceans: blue whale, fin whale, short-finned pilot whale and beluga. In all the cases, the animals were adult and two of them were pregnant. In this communication, the gross and histopathological features of a granulosa cell tumour are described in a juvenile female of Cuvier’s beaked whale (Ziphius cavirostris) found stranded in the coast of La Garrucha (Almería, Spain). Grossly, the right ovary was diffusely enlarged (6.5 x 2.5 cm) and on a sagital section was white to yellow and included both solid and cystic areas. Microscopically, the ovary was replaced by neoplastic cells arranged in variable sized lobules, cysts, nests and cords separated by dense fibrous trabeculae. The cells were round to polygonal, with vacuolated cytoplasm and round nuclei. There was mild anisokariosis and nuclear pleomorphism. Some tumour cells were arranged in radial aggregates about a central deposit of eosinophilic material (Call-Exner bodies). Other lesions observed in the animal were a moderate development of the mammary gland with normal in appearance milk secretion and mild oedema in the external genitalia. To the authors’ knowledge, this is the first description of an ovarian granulosa cell tumour in a juvenile female of Cuvier’s beaked whale (Ziphius cavirostris). Furthermore, the animal showed an unexpected mammary gland development and lactation presumably occurred secondary to oestrogen and progesterone production by the tumour.